STUDY ON HOUSING AND SETTLEMENT AREA KELURAHAN RAWA BADAK UTARA - KOJA - Wijanarko, Puji; Novalinda; Wakyudi (Border: Jurnal Arsitektur, 2020)
Urbanization is a city problem and the population continue to grow endlessly from year to year. Integrated Village is the North Jakarta Kodya village as one of the central government areas of the Republic of Indonesia, not spared from population problems (urbanization). The development of North Rawa Badak Village is inseparable from the rapid growth of the city of North Jakarta. The impact of these developments is mainly in terms of settlements, so it is known as a dense residential area that has the potential to create slums. The purpose of this study is to develop three fundamental assets of the community simultaneously: namely housing and settlement assets (a future village planning), economic assets and socio-cultural assets (rejuvenation, resettlement or rehabilitation of the environment of slums in the area). The methodology used is through quantitative and qualitative approaches called mix-method approaches. The quantitative approach is used to assess population development, population spatial density, and determinants of the level of slum area of an area which is carried out by quantitative methods such as scoring or weighting. While the qualitative approach is used to see the slum environment clusters as well as the socio-economic conditions of the community that are formed from trends due to slum criteria in the urban environment. The expected results are the drafting of the Policy and Strategy in the arrangement of the North Badak Rawa distric